2020
DOI: 10.3329/fmcj.v15i1.48999
|View full text |Cite
|
Sign up to set email alerts
|

Ligation of the Intersphincteric Fistula Tract (LIFT) Technique in the Treatment of Complex Perianal Fistula: Experience of First 50 Cases

Abstract: Perianal fistula is a common disease and surgery is the only treatment option. Many surgical techniques have been described. Ligation of intersphincteric fistula tract (LIFT) is a sphincter saving surgical technique in which fistula tract is ligated and excised through intersphincteric approach. The aim of study is to present our experience of first 50 LIFT procedures particularly healing rate, recurrence rate and complications from the procedure. This is a prospective observational study started from March 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
(53 reference statements)
0
2
0
Order By: Relevance
“…In regards to the operative time in our study, it was higher in LIFT with the mean of 50.10 minutes and lower in the case of fistulectomy with the mean of 32.14 minutes. Contrarily, the study conducted by SK Biswas 16 in which the mean operative time for LIFT was reported to be 34.7 minutes. Operative timing for LIFT in another study conducted by Vinay G. was reported to be 28.4 minutes 17 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In regards to the operative time in our study, it was higher in LIFT with the mean of 50.10 minutes and lower in the case of fistulectomy with the mean of 32.14 minutes. Contrarily, the study conducted by SK Biswas 16 in which the mean operative time for LIFT was reported to be 34.7 minutes. Operative timing for LIFT in another study conducted by Vinay G. was reported to be 28.4 minutes 17 .…”
Section: Discussionmentioning
confidence: 99%
“…However, in a study conducted by Goudar, late recurrence was seen in two completely healed patients at the same sites as the original site in LIFT at follow-up of 10 and 12 weeks 20 . SK Biswas reported seven patients who developed recurrent fistula after LIFT 16 . Faecal incontinence was categorized according to Park's classification.…”
Section: Discussionmentioning
confidence: 99%